The surplus woman : unmarried in Imperial Germany, 1871-1918 - Dollard, Catherine Leota (Monographs in German history, 2009)
The first German women's movement embraced the belief in a demographic surplus of unwed women, known as the Frauenberschuß, as a central leitmotif in the campaign for reform. Proponents of the female surplus held that the advances of industry and urbanization had upset traditional marriage patterns and left too many bourgeois women without a husband. This book explores the ways in which the realms of literature, sexology, demography, socialism, and female activism addressed the perceived plight of unwed women.